P-POSSUM as a predictor of colorectal surgical mortality in elderly patients - Gomes, A (2014)
The PPOSSUM score is considered an adequate predictor of surgical mortality in colorectal surgery. The proportion of elderly surgical patients is rising. They must be considered as a different population. Our aim was to evaluate the predictive value of P-POSSUM for colorectal surgical mortality in patients age 80 or more. Retrospective observational study. Patients with 80 years old or more who underwent colorectal surgery at our institution between 2008 and 2012 were included. Subgroup analysis was performed for malignant, urgent and elective surgery. Parametric tests were used. 202 patients were enrolled, 55% men, mean age 84,27±3,94 [80-99].Surgical mortality was 16,8%. The physiology score (PS) was 23,22±5,09; operative severity score (OS) was 13,54±4,11; predicted mortality (PM) was 8,00%±10,87. Age, PS and PM were higher among patients with surgical mortality (t=0,996 df=200 p<0,01; t=0,999 df=200 p<0,01; t=0,987 df=200 p<0,01). No differences were observed in OS. These results were also observed when subgroup analyses was done. Predicted/observed mortality ratio was 0,46 (0,58 for patients who underwent urgent surgery). P-POSSUM underestimates surgical mortality of colorectal surgery in patients 80 years or older. Higher PS was associated with surgical mortality but OS was not. This was independent of subgroup analysis.